Disability and mortality following road traffic injury: a follow-up study from a tertiary care centre of India - Chauhan, Ashish; Ahmed, Naim; Singh, Jai Veer; Singh, Vijay Kumar; Singh, Ajai; Kumar, Suresh (International Journal Of Community Medicine And Public Health, 2017)
Background: Road traffic injury (RTI) is emerging as a huge public health problem throughout the world. The problem is magnified manifold as it mainly affects people in productive age-group causing significant mortality and disability. Very few studies have been done in India to assess disability following RTI though it has attained astronomic proportions. This study was undertaken to know the proportion of disability as an outcome amongst patients admitted for road traffic injuries in a tertiary care centre of Lucknow, India and to know the determinants of mortality and disability following Road Traffic Injuries amongst these patients. Methods: A follow-up study was conducted on 267 patients of RTI admitted at Trauma Centre of King George’s Medical University UP (tertiary care centre), Lucknow, India from November 2012 to June 2013. Systemic random sampling was used to select the patients. Disability was assessed using ten points modified Barthel index. Data analysis was done using SPSS 17.0 software. Results: Mortality and disability were seen in 13.1 percent and 16.36 percent of the patients. Residence locale, road user type, time at first aid and admission, and head injury were significantly associated with mortality while extremes of age, residence locale and lower limb injury were significantly associated with disability. The level of significance was set at p value of 0.05. Conclusions: RTI poses a huge burden on healthcare delivery system and society in the form of mortality and disability. Attempts pertaining various sectors should be made to reduce the incidence of RTI and ensuing disability.